Structural and Compositional Disturbance Legacies Mediate the Resistance of European Forests to Repeated Disturbances - Kulha, Niko; Kunstler, Georges; Reineking, Björn; Peltoniemi, Mikko; Honkaniemi, Juha; Korhonen, Kari T.; Ruiz‐Benito, Paloma; Zavala, Miguel A.; Rebollo, Pedro; Barrere, Julien (Wiley-Blackwell, 2025)
Aim: Climate change is altering forest disturbance regimes across Europe. Structural and species diversity are generally thought to enhance disturbance resistance. However, how disturbances affect stand structure and tree species diversity remains untested across broad spatial gradients and for multiple disturbance agents. Furthermore, determining how disturbance-induced changes affect resistance to subsequent disturbances is critical for understanding forest dynamics in the face of global change. Location: The forests of Finland, France and Spain. Time Period: 1986–2020 ce. Major Taxa Studied: Trees. Methods: We examined the effects of tree size and tree species diversity on resistance to fire, wind, biotic and snow disturbances using a National Forest Inventory dataset of 4827 disturbed plots. We quantified disturbance resistance as the tree mortality response to different severity disturbances. We modelled the immediate disturbance-driven changes in structural and tree species diversity, and predicted how these changes affect resistance to subsequent disturbances. Results: High structural diversity increased stand resistance to snow disturbance, and high species diversity decreased resistance to fire. Severe disturbances consistently decreased structural and species diversity across all disturbance agents. However, both diversity metrics increased after low severity snow disturbances, and structural diversity increased after low severity biotic disturbance. Resistance to subsequent disturbance increased after low severity fire and low to moderate severity wind disturbances. Biotic and snow disturbance had the opposite effect, with moderate severity disturbances decreasing resistance to subsequent disturbance more than low severity disturbances. Main Conclusions: Structural and species diversity had little effect on plot-level disturbance resistance. Severe disturbances consistently decreased structural and species diversity, while low to moderate severity disturbances can increase these diversities. Resistance to subsequent disturbance is contrasted between disturbance agents and disturbance severity. Increasing disturbance severity may decrease structural and species diversity in future forests.
Keywords: disturbance dynamics; disturbance regime; forest structure; national forest inventory; resistance; sensitivity; species diversity disturbance